Efficacy of Sirolimus in Patients Requiring Tracheostomy for Life-Threatening Lymphatic Malformation of the Head and Neck: A Report From the European Reference Network - Holm, Annegret; te Loo, Maroeska; Schultze Kool, Leo; Salminen, Päivi; Celis, Veronica; Baselga, Eulalia; Duignan, Sophie; Dvorakova, Veronika; Irvine, Alan D.; Boon, Laurence M.; Vikkula, Miikka; Ghaffarpour, Nader; et al. (Frontiers in Pediatrics, 2021)
Extensive lymphatic malformations (LMs) of the head and neck region may require tracheostomy to secure the airway. Treatment of these life-threatening LMs is usually multimodal and includes sclerotherapy and surgery, among others. Recently, systemic therapy with sirolimus has been introduced as an effective treatment for venous and lymphatic malformations; its efficacy and safety profile in patients with extensive LM requiring tracheostomy are, however, as yet not fully known. We performed a retrospective, multicenter review and identified 13 patients with an extensive LM of the head and neck region, who previously underwent placement of tracheostomy and subsequently received sirolimus treatment with the aim to improve the local respiratory situation and remove the tracheostomy. Under sirolimus therapy, tracheostomy could be reversed in 8/13 (62%) patients, a further 2/13 (15%) patients improved markedly, and removal of the tracheostomy was planned at the time of writing, while 3/13 (23%) patients showed insufficient or absent response to sirolimus rendering tracheostomy reversal not feasible. The median duration of sirolimus treatment until removal of tracheostomy was 18 months (range 8 months - 5.6 years). Adverse events of sirolimus therapy were common (10/13 (77%) patients), yet the majority of these were mild (9/10 (90%)) and only one severe adverse event was recorded, with ulceration and necrosis at a catheter insertion site. In conclusion, sirolimus can be considered an effective and safe salvage treatment in patients with extensive LM even after placement of a tracheostomy, as closure of the latter was possible in the majority of patients (62%) of our retrospective cohort. A better understanding of when to start sirolimus therapy, of the duration of treatment, and of factors allowing the prediction of treatment response will require further investigation.